From hormonal immunomodulation to glioblastoma therapy: the emerging role of Ouabain - Andrade, Arthur Gomes de; Carvalho, Deyse Cristina Madruga; Magalhaes, Daniel Wilson Arruda; de Queiroz, Aline Cavalcanti; Alexandre-Moreira, Magna Suzana; Rodrigues-Mascarenas, Sandra; Cavalcante-Silva, Luiz Henrique Agra (Frontiers in Immunology, 2025)
Glioblastoma (GBM) is the most aggressive primary brain tumor in adults, characterized by rapid proliferation, diffuse infiltration, and resistance to conventional therapies. Despite advances in surgery, radiotherapy, and chemotherapy, the prognosis remains dismal, with median survival rarely exceeding 15 months. The immunosuppressive and heterogeneous tumor microenvironment (TME), along with profound tumor-intrinsic resistance mechanisms, contributes significantly to treatment failure. Cardiotonic steroids (CTS), such as ouabain, have recently gained attention for their pleiotropic effects beyond Na+/K+-ATPase inhibition, including modulation of intracellular signaling, induction of cell death, and immune regulation. In GBM, ouabain has been shown to reduce tumor cell viability, impair migration, disrupt angiogenesis, and alter different signaling pathways. Although direct evidence of ouabain’s effects on the GBM immune microenvironment is limited, findings from other models suggest that it can modulate both innate and adaptive immune responses, affecting T cells, regulatory T cells, dendritic cells, monocytes, and NK cells. While previous reviews have explored the anticancer and pharmacological aspects of cardiotonic steroids, the immunological dimension of ouabain’s activity remains underrepresented. This review integrates current evidence on ouabain’s dual actions in tumor biology and immune regulation, emphasizing its emerging therapeutic potential and the need for deeper investigation within high-grade glioma models.